Gods and agricultural scenes in the arts of Mesopotamia - مولود الحيالي فيحاء (Al-Adab Journal, 2018)
The cuneiform sources provided us with abundant information about the religious beliefs for inhabitants of ancient Mesopotamia , and their imagine about the universe and its phenomena , and which can be said that religion in ancient times characterized by specific characteristics comes in front of it the principle of vitality , which said about the existence of invisible and vivid forces in various natural and cosmic phenomena, and all powers embodied in gods , also this religion characterized in the principle of analogy , which likened those gods with human beings and their actions except death , which has become a feature of the human being while retained gods in immortality , and the multiplicity of cosmic and natural phenomena , therefore , which also describing religion in Mesopotamia with the principle of polytheism , and they linked all of them with agriculture and development and agricultural tools and connected them with religious beliefs , and put each god for them as for grain in general also some gods put to some of the tools used in agriculture as well as water channels, sheep, cattle and other things that has to do with the agricultural life and wrote many legends, stories and literary which spoke more or less about agriculture and its works .